2016
DOI: 10.1371/journal.pntd.0004513
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Scoring Model for Leptospirosis in Resource Limited Settings

Abstract: BackgroundLeptospirosis is a zoonotic infection with significant morbidity and mortality. The clinical presentation of leptospirosis is known to mimic the clinical profile of other prevalent tropical fevers. Laboratory confirmation of leptospirosis is based on the reference standard microscopic agglutination test (MAT), direct demonstration of the organism, and isolation by culture and DNA detection by polymerase chain reaction (PCR) amplification. However these methods of confirmation are not widely available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 5 publications
3
18
1
Order By: Relevance
“…The vast variations in clinical presentations hinder the early accurate diagnosis, hence laboratory confirmation is critically needed to support the manifested signs and symptoms for initiating the treatment. In the present study, 92/165 patients with clinical manifestations suggesting leptospirosis were confirmed https://doi.org/10.1371/journal.pntd.0008197.g001 .07, which is in agreement with several other studies that ranged between 38.9-45 years [23][24][25][26][27]. About two thirds of the patients (n = 60; 65%) were males as observed in most studies [24-26, 28, 29].…”
Section: Discussionsupporting
confidence: 91%
“…The vast variations in clinical presentations hinder the early accurate diagnosis, hence laboratory confirmation is critically needed to support the manifested signs and symptoms for initiating the treatment. In the present study, 92/165 patients with clinical manifestations suggesting leptospirosis were confirmed https://doi.org/10.1371/journal.pntd.0008197.g001 .07, which is in agreement with several other studies that ranged between 38.9-45 years [23][24][25][26][27]. About two thirds of the patients (n = 60; 65%) were males as observed in most studies [24-26, 28, 29].…”
Section: Discussionsupporting
confidence: 91%
“…13 The following were found to be independently associated with leptospirosis, when compared with other fevers with a similar clinical picture: history of exposure, serum creatinine >150mol/L, neutrophil differential percentage 14 >82.8%, platelet count 14 <85000mm 3 , and serum bilirubin >27U/L (Nagelkerke R square -0.567, Hosmer-Lemeshow test for goodness of fit -chi square = 2.898, p = 0.941). Notably, very few clinical or investigation characteristics reliably differentiate leptospirosis from non-leptospirosis fevers.…”
Section: Challenges In Diagnosismentioning
confidence: 90%
“…This clinical observation may usefully complete a model recently elaborated for diagnosis of leptospirosis, based on clinical features and standard laboratory test results. 19 Our study has several major limitations. First, the retrospective design exposed to misclassification bias, including patients with early recovery, or compensated severe sepsis, a prospective data collection for our definition would be more rigorous.…”
Section: Discussionmentioning
confidence: 92%